Quinoidal Azaacenes: 99 % Diradical Character. (28th April 2020) - Intorp, Sebastian N.; Hodecker, Manuel; Müller, Matthias; Tverskoy, Olena; Rosenkranz, Marco; Dmitrieva, Evgenia; Popov, Alexey A.; Rominger, Frank; Freudenberg, Jan; Dreuw, Andreas; Bunz, Uwe H. F.
Abstract: Quinoidal azaacenes with almost pure diradical character ( y= 0.95 to y= 0.99) were synthesized. All compounds exhibit paramagnetic behavior investigated by EPR and NMR spectroscopy, and SQUID measurements, revealing thermally populated triplet states with an extremely low‐energy gap Δ E ST′ of 0.58 to 1.0 kcal mol −1 . The species are persistent in solution (half‐life≈14–21 h) and in the solid state they are stable for weeks. Abstract : Best of two worlds : Lateral fusion of azaacenes onto a quinoidal system furnishes stable diradicals with a radical character ( y ) of up to 0.99. All compounds exhibit paramagnetic behavior as determined by EPR and NMR spectroscopy and SQUID measurements, revealing thermally populated triplet states with an extremely low‐energy gap Δ E ST of 0.58 to 1.0 kcal mol −1 . The species are persistent in solution (half‐life≈14–21 h), and they are stable for weeks in the solid state.